Cyclobutane and thiazole substituted Schiff base ligands and their cobalt(II), copper(II), nickel(II), and zinc(II) complexes - Yilmaz, I; Çukurovali, A (Taylor & Francis Inc, 2003)
Two novel bidentate Schiff base ligands containing cyclobutane and 2,4-disubstituted thiazole rings, 4-(1-methyl-1-p-xylylcyclobutane-3-yl)-2-(2-hydroxybenzylidenehydrazino)thiazole ((LH)-H-1), 4-(1-methyl-1-p-xylylcyclobutane-3-yl)-2-(2-hydroxy-5-bromobenzylidenehydrazino)thiazole ((LH)-H-2), and their mononuclear complexes with a 1:2 metalaigand ratio have been prepared with acetate salts of Co(II), Cu(II), Ni(II) and Zn(II) in ethanol. The authenticity of the ligands and their complexes have been established by microanalyses, IR, H-1 and C-13 NMR spectra, and by magnetic susceptibility measurements. The thermal properties of all complexes have been studied by TGA and DSC techniques. All the complexes were found to be mononuclear.
Keywords: cyclobutane; thiazole; Schiff base; complexes